NEURAXIAL TECHNIQUE FOR LABOR ANALGESIA: CURRENT TRENDS - Sivevski, Atanas (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2023)
Intense pain during labor can cause some adverse effects in parturient, like uncoordinated uterine contractions, prolonged duration, or stalled labor, as one of the most important reasons leading to caesarean section (C-S) worldwide. Unrelieved labor pain, which can lead to post-traumatic stress disorder or postpartum depression, in addition to discomfort, causes physiological stress that has an adverse effect on the mother and the newborn. Unrelieved pain stimulates catecholamine release, it causes hyperventilation and hypocapnia, which further constricts uterine blood vessels, reduces ventilation stimulus between contractions, causing a leftward shift of the oxygen dissociation curve; and all these phenomena compromise oxygen supply to the fetus, leading to fetal hypoxemia. Premature “movement down” of the fetus can lead to a canal trauma and injury during childbirth; parenteral opioids may exacerbate maternal respiratory depression, while regional (neuraxial) analgesia may reduce adverse effects of labor pain and sympathetic system responsiveness. Therefore, good labor analgesia aims not only to reduce the pain and suffering of the parturient, but also decreases the risk of fetal acidemia and, in general, makes the labor process safer, both for the mother and neonate.